Pathways for the carbon peak of resource-based cities under an energy-water coupling relationship: A case study of Taiyuan, Shanxi Province - Lin, Gang; Jiang, Dong; Fu, Jingying; Yin, Yitong (Frontiers in Environmental Science, 2022)
The "dual carbon" goal proposes new requirements for urban development, and the contradiction between high-speed urban development and environmental problems is becoming increasingly critical. The path of green and low-carbon development urgently needs to be investigated. In this paper, a simulation system of urban carbon emission based on system dynamics is built from four perspectives of population, economy, water resources and energy, aiming at building a method system for carbon peak path that is universally applicable to resource-based cities from a systematic perspective. This paper designs five scenarios: business as unusual scenario (BAU), adjustment of industrial structure (CPA1), adjustment of energy structure (CPA2), reduce energy consumption per unit of GDP (CPA3) and comprehensive management (CPAcomprehensive). Compared with the other four scenarios, the comprehensive scenario had the best coordination benefit for the coupling system, which took into account economic development, resource consumption and carbon emission reduction and could promote the realization of a carbon peak in Taiyuan city in 2029, and the comprehensive scenario will reduce CO2 by 17.14 million tons, water consumption by 158 million m3, energy consumption by 5.58 million tons of standard coal and economic growth by 175.21 billion yuan in 2029.